Authors (The Biblical archaeology review, 2022)
Ahmad Al-Jallad (Jesus in Arabia: Tracing the Spread of Christianity into the Desert) is Professor of Arabic Studies at The Ohio State University. He focuses on the languages and writing systems of pre-Islamic Arabia and the ancient Near East.